Development of river water quality management using fuzzy techniques: a review - Che Osmi S.F.; Malek M.A.; Yusoff M.; Azman N.H.; Faizal W.M. (Taylor and Francis Ltd., 2023)
decision support system; expert system; fuzzy mathematics; river management; river water; uncertainty analysis; water quality